Identification of confounders in the association between self-reported diseases and symptoms and self-rated health in a group of factory workers Identificação de variáveis de confusão na associação entre doenças e/ou sintomas referidos e auto-avaliação de saúde entre trabalhadores de uma indústria - Doroteia Aparecida Höfelmann; Nelson Blank (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Self-related health is an important predictor of morbidity and mortality, and much of its effect is influenced by the presence of chronic diseases and/or symptoms. The current study aimed to identify confounders in the association between reported chronic diseases and/or symptoms and self-rated health among workers at a metallurgical factory in Santa Catarina State, Brazil. The study design was cross-sectional, with a probabilistic sample of 482 workers. The information was obtained through a self-administered questionnaire and anthropometric measurements. Hierarchical multiple logistic regression models were adjusted. The response rate was 98.6% (n = 475), with 84.8% men, mostly employed on the factory floor (79.4%). Back pain was the most common complaint. The association between chronic diseases and self-rated health showed an odds ratio (OR) of 7.3 (95%CI: 3.7;14.5). After statistical modeling, psychosocial (-25.59%), socioeconomic (-9.29%), and occupational variables (10.54%) were identified as confounders between the outcome and chronic diseases and/or symptoms. The way diseases and/or symptoms act on self-rated health among workers transcends physical aspects. A auto-avaliação de saúde representa importante preditor de morbimortalidade, sendo grande parte de seus efeitos influenciados pela presença de doenças crônicas e/ou sintomas. Objetivou-se identificar os fatores que confundiram a associação entre doenças crônicas e/ou sintomas referidos e a auto-avaliação de saúde entre trabalhadores de uma indústria metal-mecânica de Santa Catarina, Brasil. Estudo transversal com amostra probabilística de 482 trabalhadores. As informações foram obtidas usando-se questionário auto-administrado e medidas antropométricas. Foram ajustados modelos hierarquizados de regressão logística múltipla. A taxa de resposta foi de 98,6% (n = 475), 84,8% homens, empregados no setor produtivo (79,4%). Dor nas costas foi a queixa mais comum. A associação entre doenças crônicas e auto-avaliação de saúde apresentou uma razão de chances de 7,3 (IC95%: 3,7; 14,5). Após modelagem estatística, variáveis psicossociais (-25,59%), sócio-econômicas (-9,29%) e ocupacionais (10,54%) foram identificadas como fatores de confusão entre o desfecho e doenças crônicas e/ou sintomas. A forma como as doenças e/ou sintomas atuam na auto-avaliação de saúde entre trabalhadores transcende aspectos físicos.